THE EFFECT OF MICROMETRIC PROPERTIES AND SPECIFIC GRAVITY MEASUREMENT METHODS ON PHARMACEUTICAL RAW MATERIALS: A REVIEW - Fatimah Ali; Ika Lismayani Ilyas; Ines Septiani Pratiwi (Journal Pharmaceutical Science and Application, 2025)
Background: Tablet preparations consist of active substance compositions with or without additional substances (excipients). Micrometric properties are taken into consideration in the development of solid formulations because they can play a role in formulating formulations to obtain optimal therapeutic targets and ranges to form products that can be fully developed. In selecting a tablet manufacturing method, namely the direct compression method, it is very necessary to have a substance that has good flowability and compressibility. Objective: In this study, observations were made on the poor micrometric properties in order to increase the specific gravity of the particles used so that an optimal drug formulation is obtained. Methods: The writing method used is a comparative method by collecting various sources obtained from research journals from 2014-2024. Results: Observations of micrometric properties can increase along with modifications to substances or compounds, namely by using the carboxymethylation, crystallization, and agglomeration methods. Conclusion: Pharmaceutical raw materials that have poor micrometric properties can be improved by modifying them either through carboxymethylation, crystallization, or agglomeration processes. So that it can reduce the Carr index and increase the Hausner ratio of the material, then the specific gravity test provides information about the purity of the compound. Keywords: Micrometric; Specific gravity; Carboxymethylation; Crystallization; Agglomeration.